UPAYA PENEGUHAN EKSISTENSI AHMADIYAH MELALUI PENDIDIKAN KELUARGA - Muh Azkar (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2019)
The assertion of the MUI on Ahmadiyya heresy seems to have been the legitimator of various repressive actions carried out by the majority group. Conflicts and violence against the Ahmadiyya minority groups have often occurred in various regions in Indonesia. Ironically the violence that continues to occur as if it does not find a solution. In Lombok (NTB) until now the victims of violence in 2006 were still refugees, even without obtaining civil rights as citizens. On the other hand, various forms of pressure faced by the Ahmadiyya community actually fostered solidarity among them. Even in the context of belief, this is a form of examination. If so, the teachings and beliefs of the Ahmadiyya will always exist. Coupled with the educational efforts made in the family towards children as the next generation, the existence of the Ahmadiyya movement will be maintained. This research was conducted with a qualitative approach to the type of case study. Data collection is done through observation, interviews, and documentation. The results showed that religious learning took place in the family of the Ahmadiyya Wisma Wisma Transito Mataram. Religious learning is carried out by parents individually in their families and collectively in an institution called